Identifikasi Kesiapan Masyarakat Desa Cisarua Kecamatan Sukaraja Kabupaten Sukabumi Menuju Desa Mandiri Tahun 2021 - Alya Muthia Fadhilah (Jurnal Riset Ilmu Ekonomi dan Bisnis, 2022)
Abstract. The successful process of strengthening independence in managing village resources will improve the ability of the community to maintain welfare without having to rely on others. In order for the development of the village to achieve the target of independence and welfare of the village community, it is necessary to conduct preliminary research on community readiness. This research aims to analyze the readiness of the people of Cisarua Village sukaraja district of Sukabumi regency towards independent villages in 2021 and to determine the dimensions of readiness that are most dominant for the people of Cisarua Village Sukaraja District Sukabumi to independent village in 2021. The research method used is qualitative descriptive. Data collection is carried out through interviews, questionnaires, observations and documentation to 1 village head, 3 village officials and 96 communities. Readiness assessment uses the dimensions of the Community Readiness Model and with the scale of likert scale measurement. The results of the analysis showed the Readiness of the Cisarua Village Community of Sukaraja District of Sukabumi Regency which is based on 5 dimensions of readiness to be at the initation stage for the assessment of the level of knowledge of the community is at level 3.4 which is at the Preparation stage. For the assessment of the leadership level is at the level of 3.9 which is at the initation stage. For climate-related assessments of the community is at the level of 3.3 which is at the Preparation stage. For the assessment of the level of public knowledge about the issue is at the level of 3.3, which is at the Preparation stage. And for resource-related assessment is at the level of 3.7 which is at the Initation stage. The dimension of readiness of the people of Cisarua Village of Sukaraja District of Sukabumi Regency is most dominant in the leadership dimension with the highest score of 3.9 which is included at the Initiation level. It shows the need for continuous improvement to achieve independent villages. Abstrak. Berhasilnya proses penguatan kemandirian dalam mengelola sumber daya desa akan meningkatkan kemampuan masyarakat dalam mempertahankan kesejahteraan tanpa harus bergantung pada pihak lain. Agar pengembangan desa dapat mencapai sasaran kemandirian dan kesejahteraan masyarakat desa maka perlu dilakukan penelitian awal mengenai kesiapan masyarakat. Penelitian ini bertujuan untuk menganalisis kesiapan masyarakat Desa Cisarua Kecamatan Sukaraja Kabupaten Sukabumi menuju desa mandiri tahun 2021 dan untuk menentukan dimensi Kesiapan yang paling dominan bagi masyarakat Desa Cisarua Kecamatan Sukaraja Kabupaten Sukabumi menuju desa mandiri tahun 2021. Metode penelitian yang digunakan adalah deskriptif kualitatif. Pengumpulan data dilakukan melalui wawancara, kuesioner, observasi dan dokumentasi kepada 1 Kepala desa, 3 Aparat Desa dan 96 Masyarakat. Penilaian kesiapan menggunakan dimensi Community Readiness Model dan dengan skala pengukuran skala likert. Hasil analisis menunjukkan Kesiapan Masyarakat Desa Cisarua Kecamatan Sukaraja Kabupaten Sukabumi yang didasarkan pada 5 dimensi kesiapan berada ada pada tahap initation untuk penilaian tingkat pengetahuan masyarakat berada pada tingkatan 3,4 yaitu berada pada tahap Preparation. Untuk penilaian tingkat kepemimpinan berada pada tingkatan 3,9 yaitu berada pada tahap Initation. Untuk penilaian terkait iklim masyarakat berada pada tingkatan 3,3 yaitu berada pada tahap Preparation. Untuk penilaian tingkat pengetahuan masyarakat mengenai isu berada pada tingkatan 3,3 yaitu berada pada tahap Preparation. Dan untuk penilaian terkait sumber daya berada pada tingkatan 3,7 yaitu berada pada tahap Initation. Dimensi Kesiapan masyarakat Desa Cisarua Kecamatan Sukaraja Kabupaten Sukabumi yang paling dominan berada pada dimensi kepemimpinan dengan skor tertinggi yaitu sebesar 3,9 yang termasuk pada level Initiation. Hal itu menunjukkan masih perlunya pembenahan berkelanjutan untuk mencapai desa mandiri.